STRATEGI EDUKATIF MELALUI PENDEKATAN BERMAIN UNTUK MENINGKATKAN PEMAHAMAN AGAMA ISLAM PADA PESERTA DIDIK DI JAZEEROH PITHAYANUSORN SCHOOL THAILAND - Ramasuci, Jesika; Mavianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Islamic Religious Education aims not only at transferring knowledge but also at shaping the character and morals of students. The play-based approach is an effective learning strategy because it can enhance students' motivation and understanding through enjoyable and interactive learning experiences. This approach integrates cognitive, affective, and psychomotor aspects, making learning more holistic and contextual. Using descriptive qualitative research with observation, interviews, and documentation techniques, the study found that play activities such as role-playing and interactive quizzes significantly improve students’ understanding of Islamic religious material. Challenges such as limited media resources and teachers' adaptation to this method can be overcome with continuous training. Therefore, the development of learning media and teacher training is essential for the successful long-term implementation of this approach. Play-based learning proves effective in facilitating religious understanding while enhancing students’ learning motivation.